Avaliação das alterações renais e intestinais induzidas pela cirurgia bariátrica em modelo experimental em ratos - Thibes, Milene Subtil Ormanji [UNIFESP] (2016)
Bariatric surgery is a safe and effective treatment option for those affected by morbid obesity. However, one of the long-term complications after the procedure is an increased risk of developing kidney stones, due to excessive urinary oxalate excretion. The potential underlying mechanisms for hyperoxaluria have not yet been fully clarified, but may comprise increased intestinal oxalate absorption consequent to decreased calcium intake or increased dietary oxalate, fat malabsorption, changes in the gut flora (lower colonization by oxalate-degrading bacterium), and altered intestinal oxalate transport. Slc26a3 is an oxalate transporter responsible for active oxalate uptake along the small intestine, and the phenotype of these transporter knock-out mice is characterized by reduced urinary oxalate. On the other hand, knock-out of Slc26a6, an oxalate transporter responsible for active oxalate secretion along the small intestine results in mice exhibiting hyperoxaluria. The present study aimed to investigate urinary oxalate excretion (and other lithogenic parameters), fecal fat excretion and the expression of the intestinal oxalate transporters Slc26a3 and Slc26a6 in a bariatric surgery model in rats. Male Wistar rats underwent bariatric surgery (BS) or Sham procedure, as control. After recovery, the animals were randomized to different diets. Four (4) groups were fed a high fat diet with 1.0% sodium Ox (BS-F+Ox, n=7 and Sham-F+Ox, n=7) or without it (BS-F, n=t and Sham-F, n=7) for 8 weeks. The remaining 2 groups were maintained under standard chow (BS, n=7 and Sham, n=7) for the same period. One week before surgery (baseline) and at the end of protocol (final period), 24-hour urine and feces collections were obtained for urinary biochemical and fecal fat analysis by steatocrit technique. The urinary supersaturation risk of calcium oxalate [AP(CaOx)] was also calculated. At the end of protocol, the animals were euthanized, and a single fragment was retrieved from the biliopancreatic limb (5 cm before the gastrojejunal anastomosis), alimentary limb (5 cm after the anastomosis) and colon, for quantification of expression of Slc26a3 and Slc26a6 transporters by polymerase chain reaction. At final period, bariatric rats fed with fat presented steatorrhea, irrespective of oxalate supplementation. In bariatric animals fed with fat + oxalate, final urinary oxalate and calcium oxalate supersaturation risk was markedly and significantly increased versus baseline and higher than Sham animals under the same diet and from both bariatric groups under different diets. Slc26a3 was decreased in biliopancreatic limbs of bariatric rats, as a consequence to physiological adaptations imposed by the restriction of food passage through the surgery in this intestinal segment, but Slc26a6 was not altered in any harvested intestinal fragment. In conclusion, the present study suggested that bariatric animals under conditions of a high fat and oxalate diet, induced steatorrhea and a marked and significant increase in urinary oxalate and calcium oxalate supersaturation risk, but Slc26a3 and Slc26a6 oxalate transporters did not contribute to increase urinary oxalate in this rat model. Based on present findings, we speculate that hyperoxaluria after bariatric surgery is a consequence of both fat malabsorption induced by surgery and increased intestinal dietary oxalate absorption, possibly due to enhanced paracellular permeability, suggesting that bariatric patients may benefit from a low-fat and low-oxalate diet